OIMS base self-describing metadata schema - Kruseman, Gideon; Laporte, Marie-Angelique (2023)
The Open Ontology-Based Interoperable Information Asset Metadata Schema (OIMS) is a flexible and extensible metadata schema designed to standardize and organize metadata for various information assets like datasets, documents, models, and publications, making them more accessible, transparent, and reusable. The OIMS self-describing metadata schema represents the foundational framework for annotating diverse data assets with metadata that adhere to FAIR principles. The schema is built on a JSON format for its lightweight and human-readable characteristics, and is enhanced by GTREE tags for improved readability and structure. This approach guarantees ease of use across various programming languages and platforms. Critical to the schema are its attributes, which are meticulously defined to ensure transparency and adaptability. These include required core attributes, context-specific required attributes for incorporating controlled vocabularies and ontology terms, and optional attributes that enhance usability and transparency, such as comments and attribute statuses. The schema is designed to be ontology agnostic, allowing flexibility in tagging and cross-domain application, while also setting the stage for incorporating comprehensive ontology terms in the future. Importantly, the schema is structured to support backward compatibility, recognizing the need to manage legacy data effectively.